Types of Expressive Act Found in â€œFree Guyâ€ Movie - Desinta Sitohang; Robby Satria (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The goal of this research is to describe different types of expressive speaking acts in â€œFree Guyâ€ movie. It is a part of the descriptive qualitative methodology. The observational approach and non-participatory technique were used in this study's data collection. As a method and approach for data analysis, the referential identity method and pragmatic competence-in-equalizing technique were used. This study employed the (Searle, 1969) theory of expressive acts. The study's findings indicate that â€œFree Guyâ€ movie has three different types of expressive speech acts. There were 4 data for compliment, 3 data for thanking, and 4 data for greeting